Periprosthetic tibial fractures in total knee arthroplasty – an outcome analysis of a challenging and underreported surgical issue - Anna Janine Schreiner; Florian Schmidutz; Atesch Ateschrang; Christoph Ihle; Ulrich Stöckle; Björn Gunnar Ochs; Christoph Gonser (BMC Musculoskeletal Disorders, 2018)
Abstract Background Periprosthetic fractures after total knee arthroplasty (TKA) are an increasing problem and challenging to treat. The tibial side is commonly less affected than the femoral side wherefore few studies and case reports are available. The aim of this study was to analyze the outcome of periprosthetic tibial fractures and compare our data with current literature. Methods All periprosthetic tibial TKA fractures that were treated at our Level 1 Trauma Center between 2011 and 2015 were included and analyzed consecutively. The Felix classification was used to assess the fracture type and evaluation included the radiological and clinical outcome (Knee Society Score/KSS, Oxford Knee Score/OKS). Results From a total of 50 periprosthetic TKA fractures, 9 cases (7 female, 2 male; 2 cruciate retaining, 7 constrained TKAs) involving the tibial side were identified. The mean age in this group was 77 (65–85) years with a follow-up rate of 67% after a mean of 22 (0–36) months. The Felix classification showed type IB (n = 1), type IIB (n = 2), type IIIA (n = 4) and type IIIB (n = 2) and surgical intervention included ORIF (n = 6), revision arthroplasty (n = 1), arthrodesis (n = 1) and amputation (n = 1). The rate of adverse events and revision was 55.6% including impaired wound healing, infection and re-fracture respectively peri-implant fracture. Main revision surgery included soft tissue surgery, arthrodesis, amputation and re-osteosynthesis. The clinical outcome showed a mean OKS of 29 (19–39) points and a functional/knee KSS of 53 (40–70)/41 (17–72) points. Radiological analyses showed 4 cases of malalignment after reduction and plate fixation. Conclusions Periprosthetic tibial fractures predominantly affect elderly patients with a reduced bone quality and reveal a high complication rate. Careful operative planning with individual solutions respecting the individual patient condition is crucial. If ORIF with a plate is considered, restoration of the correct alignment and careful soft tissue management including minimal invasive procedures seem important factors for the postoperative outcome.